Adipose Tissue-Derived Stromal Vascular Fraction Increases Osteogenesis in an Experimental Design Zygomatic Bone Defect Model. Issue 8 (November 2017) - Toplu, Gaye; Ozcelik, Derya; Serin, Merdan; Erdem, Havva; Topacoglu, Arzu Turkseven
Abstract : Introduction: Facial bone defects are frequently encountered problems in clinical practice. Bone grafts, flaps, and alloplastic materials are often used in their treatment. This leads to donor site morbidity and prolongation of the operation. The authors have planned this study to examine whether adipose tissue derived stromal vascular fraction (SVF) has an osteogenic effect in the critical sized membranous bone defect of the zygomatic bone. Materials and Methods: Twenty male Wistar Albino rats were used. Bilateral zygomatic arches were opened with lateral incisions. A standard 3-mm bone defect was created bilaterally on the zygomatic arches of the rats. In the experiment side, the stem cell-rich SVF that was obtained by applying centrifugal process to the adipose tissue derived from the inguinal fat pad was injected into the site of the right zygomatic arch bone defect. In the control side, left zygomatic arch was left for secondary bone healing without any treatment after a 3-mm critical bone defect was created. In the postoperative 10th (n:5) and 20th weeks (n:13), the healing areas of bone defects were assessed by a 3-dimensional tomography, and then, the rats were sacrificed and bone healing was examined histologically. Results: There were no statistically significant differences on the 10th week results. At the 20th week new bone formation amount calculated from the 3-dimensional computed tomography results was significantly higher in the experiment side ( P  = 0.033). In the histological examination at the 20th week, there was significantly more callus formation in the experiment side ( P  = 0.0112). Discussion: Stem cells can increase the rate of bone healing by differentiating into certain tissues. It is predicted that adipose tissue-derived SVF rich with mesenchymal stem cells can increase bone healing in facial bone defects and this application could replace the use of bone grafts and flaps in clinical practice. As a result, it is concluded that adipose tissue-derived stem cells can potentiate osteogenesis and reduce the possibility of developing necrosis on the bone ends.